Creating Client Extranets with SharePoint 2003 - Gerow, Mark (Apress : Imprint: Apress, 2006)
Creating Client Extranets with SharePoint 2003 is a guide for creating client-facing extranets using SharePoint 2003. This book serves as a how-to for building full-featured extranets using SharePoint 2003 and .NET technologies. If you already have experience developing and deploying business applications in .NET, then this book will help you master the intricacies of SharePoint 2003 development and customization. This is the only book of its kind-one designed to help you build a functioning client extranet from start to finish, avoiding many inherent traps in SharePoint development. It contains numerous valuable tips, tricks, and traps. And it offers various working code samples to help you get up to speed quickly using the SharePoint object model and Web Services. It uniquely focuses on SharePoint as a corporate development platform, while other books tend to focus only on end-user features.